Functional Activity of Neutrophils in Burn Sepsis - I. V. Obraztsov; M. A. Godkov; V. V. Kulabukhov; G. A. Vladimirova; D. Yu. Izmailov; E. V. Proskurnina (Общая реаниматология)
A complex effect of thermal trauma on the immune system triggers the tendency to develop and generalize infection in patients with severe thermal trauma. The phagocytic system, which is represented, first of all, by neutrophilic granulocytes, is significantly altered. Objective: to determine the dynamics of changes in the functional activity of neutrophils in patients with thermal trauma, as well as its prognostic significance in the development of purulent-septic complications of a burn disease. Materials and methods. The functional activity of neutrophils was assessed by spontaneous and induced chemiluminescence responses of whole blood sequentially stimulated with phorbol-12-myristate"13-acetate(PMA) and N-formyl-methionyl-leucyl-phenylalanine (fMLP). 34 patients with a burn disease of different severity were dynamically examined during observation. Results. The newly developed technique was applied to study the responses of whole blood of patients with burn disease to stimuli; data on the functional activity of neutrophils depending on various severities of the disease and response dynamics were obtained. Analysis of chemiluminescent curves of the development of respiratory explosion of neutrophils helped to reveal parameters of the immune system state, namely: a one— or two-phase response to a stimulus, a «rapid phase» neutrophil specific activity, and a «slow phase» neutrophil specific activity. Conclusion. The results revealed trends in alterations of functional activity of neutrophils in burn disease. Diagnostic and prognostic indices of the functional activity of neutrophils for assessing the severity of the disease and the prognosis of the septic process were suggested.